KIF22 in the Prognosis and Immune Biomarking of Pan-Cancer - Xiuhong Guo; Huayue Cao; Mei Hu; Yuening Wu; Jingxiang Li (Journal of Immunology Research)
KIF22, also known as kinesin-like DNA-binding protein (Kid), is a member of the Kinesin superfamily proteins (KIFs). Available evidence indicated that KIF22 was associated with cancer occurrence and development. However, the functions and underlying mechanisms of KIF22 in carcinogenesis and cancer progression remain largely unknown. In this study, we examined the expression profile and methylation status of KIF22 in different cancers, as well as its associations with prognosis, tumor stemness, genomic heterogeneity, immune evasion, immune infiltration, and therapeutic response in various tumor types. The results demonstrated that the expression level of KIF22 was higher in tumors than nontumor tissues and had strong relationships with prognosis, genomic heterogeneity, tumor stemness, neoantigen, ESTIMATE, and immune infiltration. KIF22 methylation status showed strong relationships with immunomodulators and chemokines. KIF22 had a significant relevance with drug susceptibility and could be a useful biomarker for forecasting survival probability and therapeutic reaction. Furthermore, KIF22 interaction and coexpression networks were mainly involved in cell division, cell cycle, DNA repair, and antigen processing and presentation. KIF22 could be used as a pan-cancer biomarker for clinical diagnosis, therapeutic schedule, prognosis, and cancer monitoring.